2005
DOI: 10.1079/ber2005390
|View full text |Cite
|
Sign up to set email alerts
|

DNA markers for identifying biotypes B and Q of Bemisia tabaci (Hemiptera: Aleyrodidae) and studying population dynamics

Abstract: The two most widespread biotypes of Bemisia tabaci (Gennadius) in southern Europe and the Middle East are referred to as the B and Q-type, which are morphologically indistinguishable. In this study various DNA markers have been developed, applied and compared for studying genetic diversity and distribution of the two biotypes. For developing sequence characterized amplified regions (SCAR) and cleaved amplified polymorphic sequences (CAPS) techniques, single random amplified polymorphic DNA (RAPD) fragments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 35 publications
3
113
0
1
Order By: Relevance
“…Amplification of B. tabaci biotype specific band (816 bp) from the mtCO1 gene and characteristic band sizes from enzymatic digestion of the amplified fragment (Khasdan et al 2005) confirmed our hypothesis that biotype Q B. tabaci was present in Finland in the autumns of 2006 and 2008 on imported poinsettias (Table 1). We also detected biotype Q in 12 of the 13 poinsettia greenhouses representing different parts of Sweden in 2006.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Amplification of B. tabaci biotype specific band (816 bp) from the mtCO1 gene and characteristic band sizes from enzymatic digestion of the amplified fragment (Khasdan et al 2005) confirmed our hypothesis that biotype Q B. tabaci was present in Finland in the autumns of 2006 and 2008 on imported poinsettias (Table 1). We also detected biotype Q in 12 of the 13 poinsettia greenhouses representing different parts of Sweden in 2006.…”
Section: Resultssupporting
confidence: 69%
“…PCR amplification was performed using a PTC-200 DNA engine (MJ Research, Inc. Watertown, USA). The annealing temperature for primers C1J-2195 and L2-N-3014 was 52 °C, as recommended by Khasdan et al (2005). Aliquots of the PCR products were electrophoresed in a 1% agarose gel at 90 V for 1 h in 1 ¥ Tris-acetate-EDTA buffer (TAE) to determine the amplified PCR product.…”
Section: Modified By De La Rua Et Al (2006)mentioning
confidence: 99%
See 1 more Smart Citation
“…As técnicas moleculares mais utilizadas para identifi car os numerosos biótipos que formam o complexo B. tabaci e determinar as características genéticas distintas entre eles incluem PCR (Polymorphic Chain Reaction) (Calvert et al 2001, RAPD (Random Amplifi ed Polymorphic DNA) (Khasdan et al 2005, Rekha et al 2005, AFLP (Amplifi ed Fragment Length Polymorphism) (Cervera et al 2000, Göçmen & Devran 2002 e RFLP (Restriction Fragment Length Polymorphism) (Abdullahi et al 2004, Rabello 2005.…”
unclassified
“…The method of DNA extraction was done according to [18]. The leaf samples were crushed in liquid nitrogen and extracted in 50 ml extraction buffer (200 mM tris-HCl pH 8.5, 250 mM NaCl, 25 mM EDTA, 0.5% SDS) then sodium acetate (3M) (pH 5.2) was added.…”
Section: Dna Extractionmentioning
confidence: 99%